The Role of Umbilical Cord–Derived Mesenchymal Stem Cell Secretome in Regulating Oxidative Stress and Inflammation in Skin Cells - Yuniar, Fanni; Purwaningsih, Endang; Rahmah, Nunung Ainur; Lilis, Nenden (Smart Medical Journal, 2026)
Introduction: Oxidative stress and inflammation are tightly interconnected processes that drive skin aging, impaired wound healing, and inflammatory skin disorders. Excessive reactive oxygen species (ROS) disrupt skin cell homeostasis, promote cellular senescence, and sustain inflammatory signaling, ultimately compromising skin regeneration. Umbilical cord–derived mesenchymal stem cell (UC-MSC) secretome has recently emerged as a promising cell-free therapeutic approach to modulate these pathological mechanisms.Methods: A narrative literature review was conducted using PubMed, Scopus, ScienceDirect, and Google Scholar to identify studies investigating the role of UC-MSC secretome in regulating oxidative stress and inflammation in skin cells. Search terms included combinations of “UC-MSC secretome,” “extracellular vesicles,” “exosomes,” “oxidative stress,” “inflammation,” “keratinocytes,” “fibroblasts,” and “wound healing.” studies relevant to skin biology were included based on biological relevance and mechanistic insight rather than strict methodological filtering.Results: The UC-MSC secretome, composed of soluble factors and extracellular vesicles enriched with bioactive proteins, cytokines, antioxidant enzymes, and regulatory microRNAs, consistently demonstrates antioxidant and anti-inflammatory effects in keratinocytes, fibroblasts, and melanocytes. Mechanistically, it reduces intracellular and mitochondrial ROS, activates endogenous antioxidant pathways such as Nrf2 and FOXO, preserves mitochondrial function, and NF-κB and MAPK. In vitro and in vivo studies show attenuation of UV-induced photoaging, enhanced wound healing, and protection of melanocytes from oxidative and immune-mediated damage.Conclusion: Current evidence supports UC-MSC secretome as a potent regulator of oxidative stress and inflammation in skin cells. Its cell-free nature offers advantages in safety, scalability, and therapeutic flexibility, highlighting strong translational potential for dermatology and regenerative skin medicine.